Continuous wavelet power spectrum of annual and seasonal SPEI series in the three regions. - Yuan Yue (313562); HaiFeng Liu (11725991); XiuXiang Mu (11725994); MengSheng Qin (11725997); TingTing Wang (10276238); Qi Wang (22418); YaQiong Yan (11726000) (2021)
The thick black contours depict the 5% significance level of local power relative to red noise; the cone of influence (COI), where edge effects are not negligible, is shown as a lighter shade.